Функціонування національної міфології у контексті глобалізації (на матеріалі роману Пола Остера «Ніч Оракула») - Шебуренкова, Т. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with some aspects of the USA national mythology and its influence on Paul Auster’s works. An attempt is made to ascertain functional mission of national myths and symbols in the novel «Oracle Night» in the context of globalization. For this purpose, the novel is studied in the light of the theory of myth.